Blood titanium levels in patients with large and sliding titanium implants - Martina Tognini; Harry Hothi; Stewart Tucker; Edel Broomfield; Masood Shafafy; Panos Gikas; Anna Di Laura; Johann Henckel; Alister Hart (BMC Musculoskeletal Disorders, 2022)
Abstract Background Titanium, which is known to be a highly biologically inert element, is one of the most commonly used metals in orthopaedic implants. While cobalt and chromium blood metal ion testing is routinely used in the clinical monitoring of patients with metal-on-metal hip implants, much less is known about the levels of titanium in patients with other implant types. The aim of this study was to better understand the normal ranges of blood titanium levels in patients implanted with large and sliding titanium constructs by comparison with reference levels from conventional titanium hips. Methods This study examined data collected from 136 patients. Over a period of 24 months, whole blood samples were collected from 41 patients implanted with large titanium implants: long (range 15 to 30 cm) spine rods with a sliding mechanism (“spine rods”, n = 18), long bone tumour implants (“tumour implants”, n = 13) and 3D-printed customised massive acetabular defect implants (“massive acetabular implants”, n = 10). This data was compared with standard, uncemented primary titanium hip implants (“standard hips”, 15 cm long) (n = 95). Clinical, imaging and blood titanium levels data were collected for all patients and compared statistically between the different groups. Results The median (range) of blood titanium levels of the standard hip, spine rods, femoral tumour implants and massive acetabular implants were 1.2 ppb (0.6–4.9), 9.7 ppb (4.0–25.4), 2.6 ppb (0.4–104.4) and 5.7 ppb (1.6–31.5) respectively. Spine rods and massive acetabular implants had significantly greater blood titanium levels compared to the standard hips group (p < 0.001). Conclusion This study showed that titanium orthopaedic implants that are large and/or have a sliding mechanism have higher blood titanium levels compared to well-functioning, conventionally sized titanium hips. Reassuringly, the increased levels did not appear to induce adverse metal reactions. This study provides useful baseline data for future studies aimed at assessing blood titanium levels as a biomarker for implant function.